THE RELATIONSHIP BETWEEN MARKET INDICATORS (ISX INDEX, SHARE PRICE, TRADING VOLUME) AND THE FINANCIAL PERFORMANCE OF COMMERCIAL BANKS. AN ANALYTICAL STUDY OF A SAMPLE OF IRAQI BANKS FOR THE PERIOD (2014- 2023) (World Economics and Finance Bulletin, 2025)
Financial markets in the world of finance and business are closely and strongly linked to the financial performance of listed companies, most notably commercial banks, as their financial performance increases the desire and demand for investment in their shares. From this perspective, the study aimed to analyze the nature of the relationship between market indicators, represented by the Iraq Stock Exchange (ISX) index, stock prices, and trading volume, and their impact on the financial performance of commercial banks. This was due to the lack of clarity regarding the impact of the financial market on the performance of Iraqi commercial banks. To demonstrate this impact, the study was based on the hypothesis that there is no statistically significant relationship between the impact of market indicators on the financial performance of commercial banks. Through financial and statistical analysis using the SPSSv23 program, the study concluded that there is a medium to strong correlation when considering the model as a whole. However, when considering the indicators individually, it was found that most of the variables are not strongly related to financial performance at a significance level of 5%. Therefore, it can be said in general that there is no statistical relationship between the study variables. The study recommended working to increase financial disclosure and transparency by the banks in the study sample in a way that presents data and achievements in a regular and clear manner. This positive data and information are reflected more effectively in stock prices and trading volume.
Keywords: ISX; stock price index